Nano-copper modified reduced graphene oxide powder, nano-copper modified graphene copper-based composite material and preparation method of nano-copper modified reduced graphene oxide powder and nano-copper modified graphene copper-based composite material
By generating nanocopper in an aqueous environment and self-assembly with reduced graphene oxide, combined with ball milling and SPS sintering technology, the problem of uniform dispersion and insufficient interface bonding of graphene in the copper matrix is solved, and the mechanical and conductive properties of nanocopper-modified graphene copper-based composite materials are improved.
Patent Information
- Application Number
- CN202510228602.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-04-11
AI Technical Summary
The uniform dispersion and interface bonding of graphene in the copper matrix are poor, resulting in limited improvement in the performance of its enhanced copper-based composite.
Nanocopper element is generated by using a strong reducing agent in an aqueous environment, and self-assembled with reduced graphene oxide through high-speed stirring to form a nanocopper-modified reduced graphene oxide powder. The powder was ball milled and mixed with copper powder, and then nano-copper modified graphene copper-based composite material was prepared by SPS plasma discharge sintering technology.
The close combination between graphene and copper matrix is achieved, the mechanical properties and electrical conductivity of the composite material are improved, and the process is simplified, which is improved to improve the controllability of production and the applicability of large-scale production.
Smart Images

Figure CN119794342A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper-based composite materials, and in particular to a method for preparing a nano-copper modified graphene copper-based composite material. Background Art
[0002] As an important nonferrous metal, copper is widely used in modern society. With the development of society and the demand for new material performance in industry, the demand for copper in emerging fields such as photovoltaics and wind power has increased significantly. Developing advanced copper alloy materials and further improving the electrical conductivity or mechanical properties of copper are of great importance to all walks of life.
[0003] The bandgap of graphene is almost zero, and the carrier mobility is 1.5X10 4 cm2 / (V·s). Graphene not only has excellent electrical properties and perfect structure, but also exhibits unique properties in other aspects, such as outstanding thermal conductivity, high light transmittance, extraordinary strength, etc., which makes graphene a new generation of metal reinforcement phase. However, due to the strong van der Waals force between graphene, graphene is prone to agglomeration, and the density of graphene is much smaller than that of metal. The interface wettability between graphene and metal is very poor, making it difficult to achieve uniform dispersion on the metal copper matrix. In addition, the interface bonding between graphene and the metal copper matrix is weak, which hinders the development of graphene-reinforced copper-based composites.
[0004] At present, there are many methods for preparing graphene-enhanced copper-based composites, mainly including ball milling, in-situ generation, electrochemical method, melt casting, and cold rolling. Although these preparation methods have improved the performance of graphene-enhanced copper-based composites to varying degrees, there are also problems such as complex process, poor graphene dispersion, and poor interface bonding between graphene and copper. Summary of the invention
[0005] To solve the above problems, the present invention provides a method for preparing nano-copper modified reduced graphene oxide powder, comprising:
[0006] S1: the reduced graphene oxide dispersion and the copper sulfate solution are mixed evenly to obtain a mixed solution A;
[0007] S2: reducing the mixed solution A with a reducing agent to obtain a mixed solution B;
[0008] S3: adjusting the pH of the mixed solution B to 8-9 to obtain a mixed solution C;
[0009] S4: titrating the mixed solution C with an alkaline solution until the mixed solution C turns red, stirring, standing and filtering to obtain a precipitate D;
[0010] S5: repeatedly washing the precipitate D until the supernatant has a neutral pH, and drying to obtain a precipitate E;
[0011] S6: Sintering the precipitate E in an inert atmosphere to obtain nano-copper modified reduced graphene oxide powder.
[0012] Furthermore, the preparation method of the reduced graphene oxide dispersion is: fully and uniformly mixing reduced graphene oxide, polyethylene glycol and water;
[0013] Polyethylene glycol acts as a dispersant and is easily volatilized and removed when heated.
[0014] Preferably, the mass ratio of the reduced graphene oxide to the polyethylene glycol is 1:(3-8), more preferably 1:4;
[0015] Preferably, the mixing method is ultrasonic dispersion, and the time is 1-3 hours, preferably 2 hours.
[0016] Furthermore, the preparation method of the copper sulfate solution is: thoroughly mixing copper sulfate pentahydrate and water;
[0017] Preferably, the mass ratio of the copper sulfate pentahydrate to the reduced graphene oxide is (50-200):1, and more preferably 90:1.
[0018] Furthermore, in step S1, during the mixing process, mechanical stirring or electromagnetic stirring is used for mixing;
[0019] Preferably, the mixing temperature is 20-50°C, more preferably 25-40°C;
[0020] Preferably, the mixing time is 5-60 min, more preferably 10-40 min;
[0021] and / or, in step S2, the reducing agent is one or more of sodium borohydride, lithium borohydride, and lithium aluminum tetrahydride;
[0022] Preferably, the mass ratio of the reducing agent to the copper sulfate pentahydrate is 1:(5-20), more preferably 1:10;
[0023] Preferably, during the reduction process, the solution temperature is 20-50°C, more preferably 25-40°C; the stirring time is 5-30min, preferably 10-20min;
[0024] And / or, in step S3, using aqueous ammonia to adjust the pH.
[0025] And / or, in step S4, the alkaline solution is a sodium hydroxide solution.
[0026] Further, in step S5, the drying is carried out in a vacuum drying oven;
[0027] Preferably, the drying temperature is 70-90°C; more preferably 75-85°C
[0028] Preferably, the drying time is 20-40 hours; more preferably 25-35°C.
[0029] And / or, in step S6, the sintering temperature is 200-350°C; more preferably 250-300°C;
[0030] Preferably, the sintering time is 30-60 min; more preferably 40-50 min;
[0031] Preferably, the gas of the inert environment is nitrogen or argon;
[0032] Preferably, before sintering, the precipitate E is ground into powder.
[0033] Directly drying the precipitate at 200-350℃ will cause the water inside to boil and cause splashing, so it is first dehydrated at 70-90℃ and ground into powder, and then dried at 200-350℃ to remove residual PEG.
[0034] The present invention also discloses a nano-copper modified reduced graphene oxide powder, which is prepared by the above preparation method. The mass ratio of C to Cu in the nano-copper modified reduced graphene oxide powder is 1:(10-30), preferably 1:(15-25).
[0035] The present invention also discloses a method for preparing a nano-copper modified graphene copper-based composite material, comprising:
[0036] (1) The above-mentioned nano-copper modified reduced graphene oxide powder and copper powder are evenly mixed;
[0037] (2) The mixed powder described in step (1) is placed into a mold and sintered to obtain a composite material.
[0038] Furthermore, in step (1), mixing is performed by ball milling;
[0039] Preferably, the ball milling mixing method is: ball milling clockwise or counterclockwise for 20 minutes, stopping for 10 minutes, changing the direction and continuing ball milling for 20 minutes, stopping for 10 minutes, and repeating the above operation;
[0040] Preferably, the effective ball milling time is 90-180 min;
[0041] Preferably, the diameter of the grinding balls for ball milling is 2-7 mm;
[0042] Preferably, the mass ratio of the grinding balls mixed by the grinding ball mill to the mixed powder of the nano-copper modified reduced graphene oxide powder and the copper powder is (3-7): 1;
[0043] Preferably, the rotation speed of the ball milling mixing is 300-500r / min;
[0044] Preferably, the sintering is performed by SPS sintering;
[0045] Preferably, the diameter of the copper powder is 25-60 μm, more preferably 40 μm.
[0046] Furthermore, in step (2), the SPS sintering molding pressure is 1-20 MPa, and more preferably 5-15 MPa;
[0047] Preferably, the sintering molding temperature is 780°C to 900°C, more preferably 800-880°C;
[0048] Preferably, the sintering molding time is 30-90 min, more preferably 45-80 min.
[0049] The present invention also discloses a nano-copper modified graphene copper-based composite material, which is prepared by the above-mentioned preparation method;
[0050] The mass fraction of reduced graphene oxide in the composite material is 0.05-0.5wt%, the mass fraction of nano copper is 1-5wt%, and the rest is copper matrix;
[0051] Wherein, the mass fraction of reduced graphene oxide in the composite material is preferably 0.2wt%, and the mass fraction of nano copper is preferably 2wt%.
[0052] The inventive principle of the present invention is as follows: in an aqueous environment, a strong reducing agent is used to reduce a nano copper element in a compound, and the nano copper and reduced graphene oxide are self-assembled by high-speed stirring + sedimentation, and the nano copper particles are deposited on the wrinkles of the graphene to form a reinforced phase powder; since reduced graphene oxide does not have good interface compatibility with metals, nano copper is introduced on the surface of reduced graphene oxide to enhance the compatibility with a copper matrix, and at the same time, the specific gravity of the original reduced graphene oxide is increased, which is more conducive to subsequent uniform dispersion by ball milling, thereby achieving improved mechanical properties; reduced graphene oxide has excellent conductivity, and nano copper is not considered an impurity relative to the copper matrix, so the conductivity can be improved.
[0053] Then, the nano-copper modified reduced graphene oxide powder and copper powder were mixed by ball milling process. The ball milling process adopted reciprocating intermittent ball milling. Under the premise of sufficient ball milling, the copper powder was guaranteed not to be oxidized on the surface during the high-energy ball milling process, thus ensuring the stability of the mixed powder. Finally, the nano-copper modified reduced graphene oxide powder and copper powder were sintered by SPS plasma discharge sintering to prepare nano-copper modified graphene copper-based composite materials, which effectively solved the problems of composite material molding and density, improved the bonding and density between graphene and copper matrix, and the uniform dispersion of nano-copper modified reduced graphene oxide contributed to the comprehensive improvement of mechanical properties and conductive properties of composite materials.
[0054] The nano-copper modified graphene copper-based composite material prepared by the method of the present invention has the following beneficial effects:
[0055] (1) High electrical conductivity: Graphene has excellent electronic conductivity. By modifying graphene with nano-copper and combining it with copper powder, the electrical conductivity of the composite material can be significantly improved.
[0056] (2) Improved mechanical strength: Graphene, as a nano-reinforcement phase, is evenly dispersed in the matrix through modification with nano-copper, overcoming the problem of poor wettability between graphene and the copper matrix, improving the mechanical properties of the final composite material, and making it better suitable for various complex usage scenarios.
[0057] (3) The process of the present invention is simple and controllable, and has good repeatability. The required equipment has high production capacity and low energy consumption, and is suitable for large-scale batch production. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0059] Figure 1 SEM images of nano-copper modified reduced graphene oxide powder provided in some embodiments of the present invention. DETAILED DESCRIPTION
[0060] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the present invention is specifically described below through examples. This example is only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art may make some non-essential changes and adjustments based on the contents of the above invention, which all fall within the scope of protection of the present invention.
[0061] The preparation method of the present invention is described in detail below.
[0062] A nano-copper modified graphene copper-based composite material, comprising:
[0063] 1. Preparation of Nano-copper Modified Reduced Graphene Oxide Powder
[0064] (1) Preparation of reduced graphene oxide dispersion
[0065] The reduced graphene oxide, polyethylene glycol and deionized water are fully mixed and ultrasonically dispersed to obtain a uniform dispersion of the reduced graphene oxide, wherein the mass ratio of the reduced graphene oxide to the polyethylene glycol is 1:(3-8), such as 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, preferably 1:4.
[0066] The mass ratio of reduced graphene oxide to polyethylene glycol is 1:(3-8). Within this mass ratio range, polyethylene glycol can disperse the reduced graphene oxide as much as possible, and the subsequent calcination of the powder to remove polyethylene glycol will not consume a lot of time.
[0067] (2) Place copper sulfate pentahydrate in deionized water and stir, and after fully dissolving, mix with reduced graphene oxide dispersion, and stir until the mixture is uniformly mixed, wherein the mass ratio of reduced graphene oxide to copper sulfate pentahydrate is 1:(50-200), such as 1:50, 1:100, 1:150, 1:200, preferably 1:90. The mixing and stirring temperature is 20-50°C, such as 20°C, 30°C, 40°C, 50°C, preferably 25-40°C; the stirring time is 5-60min, such as 5min, 10min, 20min, 30min, 40min, 50min, 60min, preferably 10-40min.
[0068] The ratio of reduced peroxide graphene to nano-copper was determined according to the experimental settings, and the amount of copper sulfate pentahydrate was further determined; it is more conducive to uniform mixing of the solution under stirring conditions at room temperature or in a heating environment.
[0069] (3) dissolving sodium borohydride in deionized water, stirring evenly, and mixing with the mixed solution of step (2), stirring evenly, wherein the mass ratio of copper sulfate pentahydrate to sodium borohydride is (5-20):1, such as 5:1, 10:1, 15:1, 20:1, etc., preferably 10:1; the stirring temperature is 20-50°C, such as 20°C, 30°C, 40°C, 50°C, more preferably 25-40°C, and the stirring time is 5-30min, such as 5min, 10min, 20min, 30min, preferably 10-20min. In addition to sodium borohydride, the reducing agent can also use one or more of lithium borohydride and lithium aluminum tetrahydride.
[0070] Based on the above, the amount of copper sulfate pentahydrate is determined, thereby determining the amount of reducing agent sodium borohydride; at room temperature or in a heated environment, it is more conducive to the solution to undergo a reduction reaction under stirring conditions, and the time decreases as the temperature increases.
[0071] (4) Add 10 ml of aqueous ammonia to the mixed solution of step (3), stir thoroughly, and keep the solution in an alkaline environment.
[0072] (5) Sodium hydroxide is fully dissolved in deionized water, and then slowly and uniformly added to the mixed solution obtained in step (4) until the solution turns red. After the titration, the mixture is stirred for 30 minutes and then allowed to stand to precipitate.
[0073] During the titration process, the solution gradually turns red. After the titration of the sodium hydroxide solution is completed, continue stirring for 30 minutes to allow for full reaction, and then let it stand and wait for precipitation.
[0074] (6) The precipitate obtained in step (5) is repeatedly washed until the pH of the supernatant is neutral, filtered and dried in a vacuum drying oven for 20 h to 40 h, for example, 20 h, 25 h, 30 h, 35 h, 40 h, preferably 25 to 35 h, at a drying temperature of 70° C. to 90° C., for example, 70° C., 80° C., 90° C., preferably 75 to 85° C., and then ground into powder.
[0075] The purpose of washing is to remove excess sodium hydroxide, and the purpose of sufficient drying is to remove excess water from the precipitate to form a block or powder.
[0076] (7) Sintering under an inert environment to remove residual polyethylene glycol at a sintering temperature of 200-350°C, for example,
[0077] 200°C, 240°C, 260°C, 300°C, 320°C, 350°C, preferably 250-300°C, and the sintering time is 30-60 min, for example 30 min, 40 min, 50 min, 60 min, preferably 40-50 min.
[0078] Remove excess polyethylene glycol from the powder to ensure powder purity.
[0079] Figure 1The SEM image of the nano-copper modified reduced graphene oxide powder provided for some embodiments of the present invention shows that the nano-copper particles are evenly distributed on the surface of the graphene sheet. These particles show a smaller size and a more even distribution, indicating that the preparation method effectively realizes the modification of reduced graphene oxide by nano-copper. The distribution of the nano-copper particles on the graphene sheet is more even, and the evenly distributed nano-copper particles can enhance the interface bonding between graphene and the copper matrix, thereby improving the mechanical properties and electrical conductivity of the composite material. In summary, these characteristics show that the preparation method of the present invention effectively realizes the modification of reduced graphene oxide by nano-copper, and the prepared nano-copper modified reduced graphene oxide powder has good structure and performance, and is suitable for preparing high-performance nano-copper modified graphene copper-based composite materials.
[0080] 2. Preparation of composite powder
[0081] Weigh a certain amount of the nano-copper modified reduced graphene oxide powder and pure copper powder obtained in step 1, and mix them thoroughly in a ball mill. The mass fraction of graphene is 0.05-0.5wt%, for example, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, preferably 0.2-0.4wt%; the mass fraction of nano-copper is 1-5wt%, for example, 1%, 2%, 3%, 4%, 5%, preferably 2-4wt%; the rest is copper powder.
[0082] In this step, when preparing the nano-copper modified reduced graphene oxide powder in step 1, the graphene added in the preparation process has a certain mass ratio to the copper sulfate pentahydrate, so when step 1 is completed, the mass ratio of the graphene in the nano-copper modified reduced graphene oxide powder to the nano-copper is also a fixed value. Then, the amount of the copper matrix added is determined according to the requirements for preparing the final composite material product.
[0083] In the present invention, the mass fraction of graphene is 0.05-0.5wt%, the mass fraction of nano copper is 1-5wt%, and the rest is copper powder. The amount of graphene is reduced as much as possible to achieve the effect of trace addition and substantial enhancement.
[0084] In the present invention, a planetary ball mill can be used for high-energy ball milling. The grinding balls are stainless steel grinding balls, the grinding ball diameter is 2-7mm, for example, 2mm, 3mm, 4mm, 5mm, 6mm, 7mm, the mass ratio of the ball material is (3-7): 1, for example, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, the ball milling speed is 300-500r / min, for example, 300r / min, 350r / min, 400r / min, 450r / min, 500r / min, each time the ball milling is clockwise for 20min, stop for 10min, change the direction, counterclockwise for 20min, stop for 10min, the cumulative effective ball milling time is 90-180min, for example, 90min, 100min, 110min, 120min, 130min, 140min, 150min, 160min, 170min, 180min, after the ball milling is completed, the grinding balls are sieved to obtain the composite powder. This ball milling process adopts reciprocating intermittent ball milling. This ball milling process ensures that the copper powder will not be oxidized on the surface during high-energy ball milling under the premise of sufficient ball milling, thereby ensuring the stability of the mixed powder.
[0085] 3. Preparation of copper-based composite materials
[0086] The composite powder obtained in step 2 is filled in a mold and subjected to SPS sintering. The temperature of SPS sintering is 780°C-900°C, such as 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, preferably 800-880°C; the sintering time is 30min-90min, such as 30min, 40min, 50min, 60min, 70min, 80min, 90min, preferably 45-80min; the sintering pressure is 1-20MPa, such as 1MPa, 5MPa, 10MPa, 15MPa, 20MPa, preferably 5-15Mpa. Then cool with the furnace, cool to below 80°C and take out to obtain a nano-copper modified graphene copper-based composite material. In the composite material prepared by the above method, the mass fraction of reduced graphene oxide is 0.05-0.5wt%, the mass fraction of nano copper is 1-5wt%, and the rest is copper matrix.
[0087] The mold filled with composite powder can be a graphite mold or a steel mold. The shape of the mold can be a cuboid, a cylinder, etc. It can be selected according to actual needs and is not limited here.
[0088] The preferred embodiment is described in detail below:
[0089] Embodiment 1:
[0090] A method for preparing a nano-copper modified graphene copper-based composite material, which specifically comprises the following steps:
[0091] S1: Preparation of nano-copper modified reduced graphene oxide powder
[0092] Weigh 0.5g of reduced graphene oxide and 2g of polyethylene glycol, place them in 400ml of deionized water, and ultrasonically disperse them for 2h to fully open the graphene sheets; weigh 19.7g of copper sulfate pentahydrate, place them in 500ml of deionized water, stir and dissolve, then pour them into the graphene solution after ultrasonication, place the mixed solution in a 40℃ water bath and mechanically stir for 1h to make the solution fully uniform; weigh 4g of sodium borohydride, place them in 300ml of deionized water and stir them evenly, and add them to the above mixed solution at a uniform speed, keep heating in a 40℃ water bath and mechanically stir for 10mi n; then the reaction system was placed at room temperature, and 10 ml of ammonia water was added, and stirring was continued for 5 min; 15 g of sodium hydroxide powder was weighed and dissolved in 250 ml of deionized water, and then slowly titrated into the mixture at a uniform speed; after the titration, the reaction was stirred for 30 min and then allowed to stand to precipitate, the precipitate was repeatedly washed to make the pH value of the supernatant neutral, the precipitate was vacuum dried at 70 ° C for 30 h, and after grinding, it was sintered in a tubular furnace at 250 ° C in a nitrogen environment for 40 min to remove residual PEG, and nano-copper modified reduced graphene oxide powder was obtained.
[0093] S2: Preparation of composite powder
[0094] Weigh a certain amount of nano-copper modified reduced graphene oxide powder and pure copper powder and put them in a planetary ball mill for high-energy ball milling, where the mass fraction of graphene is 0.1%, the mass fraction of nano-copper is 1%, and the rest is copper powder. Stainless steel grinding balls are used for grinding balls, the diameter of the grinding balls is 3mm, the ball-to-material ratio is 5:1, the ball milling speed is 350r / min, each time the ball milling is clockwise for 20min, stop for 10min, change the direction, counterclockwise ball milling for 20min, stop for 10min, the total ball milling is 3h, and the cumulative effective ball milling time is 120min. After the ball milling is completed, the grinding balls are sieved to obtain the composite powder.
[0095] S3: Preparation of copper-based composite materials
[0096] The composite powder obtained in S2 was filled into a graphite mold with a diameter of 60 mm, and sintered in a hot pressing sintering furnace at a temperature of 830°C and a pressure of 11 MPa for 40 minutes, and then cooled in the furnace to obtain a nano-copper modified graphene copper-based composite material.
[0097] Embodiment 2:
[0098] A method for preparing a nano-copper modified graphene copper-based composite material, which specifically comprises the following steps:
[0099] S1: Preparation of nano-copper modified reduced graphene oxide powder
[0100] Weigh 0.5g of reduced graphene oxide and 2g of polyethylene glycol, place them in 400ml of deionized water, and ultrasonically disperse them for 2h to fully open the graphene sheets; weigh 39.4g of copper sulfate pentahydrate, place them in 500ml of deionized water, stir and dissolve, then pour them into the ultrasonicated graphene solution, heat the mixture in a 40℃ water bath and mechanically stir for 1h to make the solution fully uniform; weigh 4g of sodium borohydride, place them in 300ml of deionized water, stir them evenly, and add them to the above mixture at a uniform speed, keep heating in a 40℃ water bath and mechanically stir for 10mi n; then the reaction system was placed at room temperature, and 10 ml of ammonia water was added, and stirring was continued for 5 min; 15 g of sodium hydroxide powder was weighed and dissolved in 250 ml of deionized water, and then slowly titrated into the mixture at a uniform speed; after the titration, the reaction was stirred for 30 min and then allowed to stand to precipitate, the precipitate was repeatedly washed to make the pH value of the supernatant neutral, the precipitate was vacuum dried at 70 ° C for 30 h, and after grinding, it was sintered in a tubular furnace at 250 ° C in a nitrogen environment for 40 min to remove residual PEG, and nano-copper modified reduced graphene oxide powder was obtained.
[0101] S2: Preparation of composite powder
[0102] Weigh a certain amount of nano-copper modified reduced graphene oxide powder and pure copper powder and put them in a planetary ball mill for high-energy ball milling, where the mass fraction of graphene is 0.1%, the mass fraction of nano-copper is 2%, and the rest is copper powder. Stainless steel grinding balls are used for grinding balls, the diameter of the grinding balls is 4mm, the ball-to-material ratio is 4:1, the ball milling speed is 400r / min, each time the ball milling is clockwise for 20min, stop for 10min, change the direction, counterclockwise for 20min, stop for 10min, the total ball milling is 4h, and the cumulative effective ball milling time is 160min. After the ball milling is completed, the grinding balls are sieved to obtain the composite powder.
[0103] S3: Preparation of copper-based composite materials
[0104] The composite powder obtained in S2 was filled into a graphite mold with a diameter of 60 mm, and sintered in a hot pressing sintering furnace at a temperature of 800°C and a pressure of 13 MPa for 40 minutes, and then cooled in the furnace to obtain a nano-copper modified graphene copper-based composite material.
[0105] Embodiment 3:
[0106] A method for preparing a nano-copper modified graphene copper-based composite material, which specifically comprises the following steps:
[0107] S1: Preparation of nano-copper modified reduced graphene oxide powder
[0108] Same as S1 in Example 1;
[0109] S2: Preparation of composite powder
[0110] Weigh a certain amount of nano-copper modified reduced graphene oxide powder and pure copper powder and put them in a planetary ball mill for high-energy ball milling, where the mass fraction of graphene is 0.2%, the mass fraction of nano-copper is 2%, and the rest is copper powder. Stainless steel grinding balls are used for grinding balls, the diameter of the grinding balls is 5mm, the ball-to-material ratio is 3:1, the ball milling speed is 350r / min, each time the ball milling is clockwise for 20min, stop for 10min, change the direction, counterclockwise ball milling for 20min, stop for 10min, the total ball milling is 3.5h, and the cumulative effective ball milling time is 140min. After the ball milling is completed, the grinding balls are sieved to obtain the composite powder.
[0111] S3: Preparation of copper-based composite materials
[0112] The composite powder obtained in S2 was filled into a graphite mold with a diameter of 60 mm, and sintered in a hot pressing sintering furnace at a temperature of 850°C and a pressure of 10 MPa for 40 minutes, and then cooled in the furnace to obtain a nano-copper modified graphene copper-based composite material.
[0113] Embodiment 4:
[0114] A method for preparing a nano-copper modified graphene copper-based composite material, which specifically comprises the following steps:
[0115] S1: Preparation of nano-copper modified reduced graphene oxide powder
[0116] Weigh 0.5g of reduced graphene oxide and 2g of polyethylene glycol, place them in 400ml of deionized water, and ultrasonically disperse them for 2h to fully open the graphene sheets; weigh 29.55g of copper sulfate pentahydrate, place them in 500ml of deionized water, stir and dissolve, then pour them into the ultrasonicated graphene solution, heat the mixture in a 40℃ water bath and mechanically stir for 1h to make the solution fully uniform; weigh 4g of sodium borohydride, place them in 300ml of deionized water, stir them evenly, and add them to the above mixture at a uniform speed, keep heating in a 40℃ water bath and mechanically stir for 10mi n; then the reaction system was placed at room temperature, and 10 ml of ammonia water was added, and stirring was continued for 5 min; 15 g of sodium hydroxide powder was weighed and dissolved in 250 ml of deionized water, and then slowly titrated into the mixture at a uniform speed; after the titration, the reaction was stirred for 30 min and then allowed to stand to precipitate, the precipitate was repeatedly washed to make the pH value of the supernatant neutral, the precipitate was vacuum dried at 70 ° C for 30 h, and after grinding, it was sintered in a tubular furnace at 250 ° C in a nitrogen environment for 40 min to remove residual PEG, and nano-copper modified reduced graphene oxide powder was obtained.
[0117] S2: Preparation of composite powder
[0118] Weigh a certain amount of nano-copper modified reduced graphene oxide powder and pure copper powder and put them in a planetary ball mill for high-energy ball milling, where the mass fraction of graphene is 0.3%, the mass fraction of nano-copper is 4.5%, and the rest is copper powder. Stainless steel grinding balls are used for grinding balls, the diameter of the grinding balls is 3mm, the ball-to-material ratio is 6:1, the ball milling speed is 380r / min, each time the ball milling is clockwise for 20min, stop for 10min, change the direction, counterclockwise for 20min, stop for 10min, the total ball milling is 4.5h, and the cumulative effective ball milling time is 180min. After the ball milling is completed, the grinding balls are sieved to obtain the composite powder.
[0119] S3: Preparation of copper-based composite materials
[0120] The composite powder obtained in S2 was filled into a graphite mold with a diameter of 60 mm, and sintered in a hot pressing sintering furnace at a temperature of 870°C and a pressure of 13 MPa for 40 min, and then cooled in the furnace to obtain a nano-copper modified graphene copper-based composite material.
[0121] Embodiment 5:
[0122] In this embodiment, the mass fraction of graphene in the composite material is 0.4%, the mass fraction of nano copper is 4%, and the remainder is copper. The other reaction conditions are the same as those in Example 1.
[0123] Embodiment 6:
[0124] A method for preparing a nano-copper modified graphene copper-based composite material, which specifically comprises the following steps:
[0125] S1: Preparation of nano-copper modified reduced graphene oxide powder
[0126] Weigh 0.5g of reduced graphene oxide and 2g of polyethylene glycol, place them in 400ml of deionized water, and ultrasonically disperse them for 2h to fully open the graphene sheets; weigh 9.35g of copper sulfate pentahydrate, place them in 500ml of deionized water, stir and dissolve, then pour them into the graphene solution after ultrasonication, place the mixed solution in a 40℃ water bath and mechanically stir for 1h to make the solution fully uniform; weigh 4g of sodium borohydride, place them in 300ml of deionized water and stir them evenly, and add them to the above mixed solution at a uniform speed, keep heating in a 40℃ water bath and mechanically stir for 10mi n; then the reaction system was placed at room temperature, and 10 ml of ammonia water was added, and stirring was continued for 5 min; 15 g of sodium hydroxide powder was weighed and dissolved in 250 ml of deionized water, and then slowly titrated into the mixture at a uniform speed; after the titration, the reaction was stirred for 30 min and then allowed to stand to precipitate, the precipitate was repeatedly washed to make the pH value of the supernatant neutral, the precipitate was vacuum dried at 70 ° C for 30 h, and after grinding, it was sintered in a tubular furnace at 250 ° C in a nitrogen environment for 40 min to remove residual PEG, and nano-copper modified reduced graphene oxide powder was obtained.
[0127] S2: Preparation of composite powder
[0128] Weigh a certain amount of nano-copper modified reduced graphene oxide powder and pure copper powder and put them in a planetary ball mill for high-energy ball milling, where the mass fraction of graphene is 0.4%, the mass fraction of nano-copper is 2%, and the rest is copper powder. Stainless steel grinding balls are used for grinding balls, the grinding ball diameter is 7mm, the ball-to-material ratio is 7:1, the ball milling speed is 450r / min, each time clockwise ball milling for 20min, stop for 10min, change the direction, counterclockwise ball milling for 20min, stop for 10min, a total of 3h of ball milling, the cumulative effective ball milling time is 120min, after the ball milling is completed, the grinding balls are sieved to obtain the composite powder.
[0129] S3: Preparation of copper-based composite materials
[0130] The composite powder obtained in S2 is filled in a graphite mold with a diameter of 60 mm, and sintered in a hot pressing sintering furnace. The temperature and pressure are maintained at 850° C. for 40 minutes, and then cooled in the furnace to obtain a nano-copper modified graphene copper-based composite material.
[0131] Comparative Example 1:
[0132] S1: Preparation of composite powder
[0133] Weigh a certain amount of graphene powder, nano copper powder and pure copper powder and put them together in a planetary ball mill for high-energy ball milling, where the mass fraction of graphene is 0.2%, the mass fraction of nano copper is 2%, and the rest is copper. Stainless steel grinding balls are used for grinding balls, the diameter of the grinding balls is 5mm, the ball-to-material ratio is 5:1, the ball milling speed is 400r / min, each time the ball milling is clockwise for 20min, stop for 10min, change the direction, counterclockwise for 20min, stop for 10min, the total ball milling is 3h, and the cumulative effective ball milling time is 120min. After the ball milling is completed, the grinding balls are sieved to obtain the composite powder.
[0134] S2: Preparation of copper-based composite materials
[0135] The composite powder obtained in S1 was filled into a graphite mold with a diameter of 60 mm, and sintered in a hot pressing sintering furnace at a temperature of 850° C. for 40 minutes, and then cooled in the furnace to obtain a copper-based composite material.
[0136] Comparative Example 2:
[0137] S1: Preparation of composite powder
[0138] Weigh a certain amount of graphene powder and pure copper powder and put them together in a planetary ball mill for high-energy ball milling, where the mass fraction of graphene is 0.4% and the rest is copper. Stainless steel grinding balls are used for grinding balls, the diameter of the grinding balls is 5mm, the ball-to-material ratio is 4:1, the ball milling speed is 450r / min, each time the ball milling is clockwise for 20min, stop for 10min, change the direction, counterclockwise for 20min, stop for 10min, the total ball milling is 4h, and the cumulative effective ball milling time is 160min. After the ball milling is completed, the grinding balls are sieved to obtain the composite powder.
[0139] S2: Preparation of copper-based composite materials
[0140] The composite powder obtained in S1 was filled into a graphite mold with a diameter of 60 mm, and sintered in a hot pressing sintering furnace at a temperature of 870° C. for 40 minutes, and then cooled in the furnace to obtain a copper-based composite material.
[0141] Comparative Example 3:
[0142] In this comparative example, graphene is replaced by conductive carbon black, and the mass fraction of the conductive carbon black is 0.2%, the mass fraction of nano copper is 2%, and the rest is copper. The other reaction conditions are the same as those in comparative example 1.
[0143] The nano-copper modified graphene copper-based composite materials prepared in Examples 1-6 and Comparative Examples 1-3 were tested for mechanical strength and electrical conductivity. The test method for electrical conductivity was the Van der Pauw method, and the electrical conductivity was expressed using the international annealed copper conductivity standard. The strength was expressed by polishing the sample according to the ASTM standard, and a tensile test was performed at a rate of 0.05 mm / s at room temperature. The tests for mechanical strength and electrical conductivity should be performed three or more times. The results are shown in Table 1.
[0144] Table 1 Tensile strength and conductivity of the composite materials prepared in the examples and comparative examples
[0145]
[0146]
[0147] It can be seen from the test data in Table 1 that the tensile strength of the nano-copper modified graphene copper-based composite material prepared in Examples 1-6 of the present invention is not less than 394MPa, and can reach up to 556MPa, and the electrical conductivity is not less than 107%IACS, and can reach up to 134%IACS. Although different carbon sources or nano-copper were added to the comparative example, the tensile strength and electrical conductivity decreased to varying degrees, and the electrical conductivity decreased by more than 17% compared with pure copper. It can be explained through the above embodiments that the method for preparing the nano-copper modified graphene copper-based composite material provided by the embodiment of the present invention achieves the synergistic improvement of the mechanical strength and electrical properties of the copper-based composite material, solves the shortcomings existing in the traditional composite method, and provides a new idea for the preparation of high-strength and high-conductivity copper-based composite materials.
[0148] In summary, the present invention performs surface modification on reduced graphene oxide by chemical plating, deposits nano copper particles containing copper compounds on the wrinkles of reduced graphene oxide, and the obtained nano copper modified reduced graphene oxide powder can be evenly dispersed in the copper matrix, and the presence of nano copper improves the wettability with the copper matrix. Therefore, the embodiment of the present invention solves the problem of graphene agglomeration and the problem of poor wettability with metallic copper, and realizes the uniform dispersion of modified graphene in copper powder by ball milling; at the same time, a preparation method for preparing nano copper modified graphene copper-based composite materials using high temperature and high pressure is provided, and the close combination of metallic copper and graphene is realized, thereby exerting the high strength of graphene to improve the strength of copper, thereby realizing the dual improvement of mechanical properties and electrical properties of graphene copper composite materials. The process of the present invention is simple and controllable, and has good repeatability, high equipment capacity, low energy consumption, and is suitable for large-scale batch production. And the chemical plating method used in the preparation of nano copper modified graphene by the present invention has not been reported yet, which provides a new idea for preparing nano copper modified graphene.
[0149] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art can still modify the technical solutions described in the above embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing nano-copper modified reduced graphene oxide powder, characterized in that: include: S1: the reduced graphene oxide dispersion and the copper sulfate solution are mixed evenly to obtain a mixed solution A; S2: reducing the mixed solution A with a reducing agent to obtain a mixed solution B; S3: adjusting the pH of the mixed solution B to 8-9 to obtain a mixed solution C; S4: titrating the mixed solution C with an alkaline solution until the mixed solution C turns red, and filtering the mixed solution to obtain a precipitate D; S5: washing the precipitate D until the supernatant has a neutral pH, and drying to obtain a precipitate E; S6: Sintering the precipitate E in an inert atmosphere to obtain nano-copper modified reduced graphene oxide powder.
2. The preparation method according to claim 1, characterized in that: The preparation method of the reduced graphene oxide dispersion is as follows: fully and uniformly mixing reduced graphene oxide, polyethylene glycol and water; Preferably, the mass ratio of the reduced graphene oxide to the polyethylene glycol is 1:(3-8), more preferably 1:4; Preferably, the mixing method is ultrasonic dispersion, and the time is 1-3 hours, preferably 2 hours.
3. The preparation method according to claim 1, characterized in that: The preparation method of the copper sulfate solution is: fully and evenly mixing copper sulfate pentahydrate and water; Preferably, the mass ratio of the copper sulfate pentahydrate to the reduced graphene oxide is (50-200):1, and more preferably 90:
1.
4. The preparation method according to claim 1, characterized in that: In step S1, during the mixing process, mechanical stirring or electromagnetic stirring is used for mixing; Preferably, the mixing temperature is 20-50°C, more preferably 25-40°C; Preferably, the mixing time is 5-60 min, more preferably 10-40 min; and / or, in step S2, the reducing agent is one or more of sodium borohydride, lithium borohydride, and lithium aluminum tetrahydride; Preferably, the mass ratio of the reducing agent to the copper sulfate pentahydrate is 1:(5-20), more preferably 1:10; Preferably, during the reduction process, the solution temperature is 20-50°C, more preferably 25-40°C; the stirring time is 5-30min, preferably 10-20min; and / or, in step S3, using aqueous ammonia to adjust the pH; And / or, in step S4, the alkaline solution is a sodium hydroxide solution.
5. The preparation method according to claim 1, characterized in that: In step S5, the drying is carried out in a vacuum drying oven; Preferably, the drying temperature is 70-90°C; more preferably 75-85°C; Preferably, the drying time is 20-40 hours, more preferably 25-35 hours; And / or, in step S6, the sintering temperature is 200-350°C; more preferably 250-300°C; Preferably, the sintering time is 30-60 min; more preferably 40-50 min; Preferably, the gas of the inert environment is nitrogen or argon; Preferably, before sintering, the precipitate E is ground into powder.
6. A nano-copper modified reduced graphene oxide powder, characterized in that: Prepared by any preparation method of rights 1-5, the mass ratio of C to Cu in the nano-copper modified reduced graphene oxide powder is 1: (10-30), preferably 1: (15-25).
7. A method for preparing a nano-copper modified graphene copper-based composite material, characterized in that: The nano-copper modified reduced graphene oxide powder according to claim 6 is used for preparation, and the preparation steps include: (1) uniformly mixing the nano-copper modified reduced graphene oxide powder and copper powder according to claim 6; (2) The mixed powder described in step (1) is placed into a mold and sintered to obtain a composite material.
8. The preparation method according to claim 7, characterized in that: In step (1), mixing is performed by ball milling; Preferably, the ball milling mixing method is: ball milling clockwise or counterclockwise for 20 minutes, stopping for 10 minutes, changing the direction and continuing ball milling for 20 minutes, stopping for 10 minutes, and repeating the above operation; Preferably, the effective ball milling time is 90-180 min; Preferably, the diameter of the grinding balls for ball milling is 2-7 mm; Preferably, the mass ratio of the grinding balls mixed by the grinding ball mill to the mixed powder of the nano-copper modified reduced graphene oxide powder and the copper powder is (3-7): 1; Preferably, the rotation speed of the ball milling mixing is 300-500r / min; Preferably, the sintering is performed by SPS sintering; Preferably, the diameter of the copper powder is 25-60 μm, more preferably 40 μm.
9. The preparation method according to claim 8, characterized in that: In step (2), the SPS sintering molding pressure is 1-20 MPa, more preferably 5-15 MPa; Preferably, the sintering molding temperature is 780°C to 900°C, more preferably 800-880°C; Preferably, the sintering molding time is 30-90 min, more preferably 45-80 min.
10. A nano-copper modified graphene copper-based composite material, characterized in that: Prepared by any preparation method of claims 7-9; The mass fraction of reduced graphene oxide in the composite material is 0.05-0.5wt%, the mass fraction of nano copper is 1-5wt%, and the rest is copper matrix; Wherein, the mass fraction of reduced graphene oxide in the composite material is preferably 0.2wt%, and the mass fraction of nano copper is preferably 2wt%.